Impact of Integrated E-learning: Traditional Approach to Teaching Engineering Perspective Courses - Fewella, Lina Nageb; Khodeir, Laila Mohamed; Swidan, Abeer Hamed (International Journal of Engineering Pedagogy (iJEP), 2021)
Abstract— The process of teaching engineering perspective courses generally faces a number of challenges due to the nature of the course, the skills required and the large number of students. Thus, this paper aims at assessing the impact of applying a traditional integrated E-learning approach to the teaching of the Engineering Perspective course based on an online system, namely the Google Classroom application. The population of this study is composed of 130 Egyptian first-year applied arts students from the nine departments of the Faculty of Applied Arts at Damietta University during the first semester of the academic year 2019-2020. The sample is determined using Google Forms via Google Classroom. A total of 130 students participated in Google Classroom class and 84 students participated in this investigation. Results revealed that the students primarily preferred the proposed approach for its technical feasibility and its positive effect on their academic performance. Where can they access academic content anytime and anywhere for an infi-nite number of times? The study resulted in a proposal for a framework de-signed to apply the integrated approach in a comprehensive manner and adapted to its application in the design of practical engineering courses in which students are enrolled in large numbers.